Gaya Belajar Ditinjau dari Tipe Kepribadian dan Jenis Kelamin - Damayanti, Andia Kusuma (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2012)
Abstract. This research was purposed to test the hipotesis: there are differences of studentsâ€™ learning style evaluated from personality type and gender. Research subjects were 100 student, consists of 50 girls and 50 boys. Measurement of independent variable applies scaleÂ personality type of temperament in this research expressed through scale developed by Littauer (1996). Measurement of dependent variable applies learning style scale V-A-K which has been developed by Bandler and Ginder ( in Gunawan, 2003). Data were analyzed by Chi Sqare and t-test. Result of analysis showed that learning style if it is evaluated from both personality type and gender there was no differences. It means that most of the students have the same tendency in the learning style either visually, auditory and also kinesthetic, if it is evaluated from their personality type and gender. Keywords: learning styles, personality types, gender